ML-9 TREATMENT OUTCOMES OF TIRABRUTINIB FOR RELAPSED AND REFRACTORY PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA IN A SINGLE INSTITUTE. (3rd December 2022) - Ohka, Fumiharu; Yamaguchi, Junya; Motomura, Kazuya; Takeuchi, Kazuhito; Nagata, Yuichi; Maeda, Sachi; Nishikawa, Tomohide; Kibe, Yuji; Shimizu, Hiroki; Saito, Ryuta
Abstract: Recent clinical studies improved prognosis of primary central nervous system lymphoma (PCNSL) using multiple treatment reagents combined with radiation therapy. However, for recurrent and refractory cases after treatment with regimen consisting of multiple reagents, potent effective treatment has not been established yet. Tirabrutinib, Bruton's tyrosine kinase inhibitor was introduced for treatment of recurrent and refractory PCNSL in Japan. However, case series study investigating the clinical outcome of PCNSL cases treated with tirabrutinib have not been reported yet excepting for phase I/II study of tirabrutinib. We treated nine recurrent and two refractory cases. In all of these cases, except for one case exhibiting severe skin rash in spite of cessation of administration of tirabrutinib, we obtained favorable overall response rate (CR or Cru=5 and PR=5) together with favorable progression free survival (median; 339 days). Five cases exhibited skin rash (CTCAE grade 3; n=2 and grade 2; n=3). Grade 3 or 2 skin rash were found on day 9 or 75 of tirabrutinib treatment, respectively. In one case, MYD88 mutations in ctDNA derived from blood plasma were turned to be negative after one week administration of tirabrutinib. Although adverse effects such as skin rash was frequently found, tirabrutinib is effective for recurrent or refractory PCNSL cases. Our data suggested that treatment response of tirabrutinib could be evaluated via evaluation of copy number analysis of MYD88 mutations in ctDNA of blood plasma.